2009
DOI: 10.1016/j.cub.2009.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Modulates the Sensory Coding of Observed Gaze Direction

Abstract: Gaze direction is an important social signal in both human and nonhuman primates, providing information about conspecifics' attention, interests, and intentions. Single-unit recordings in macaques have revealed neurons selective for others' specific gaze direction. A parallel functional organization in the human brain is indicated by gaze-adaptation experiments, in which systematic distortions in gaze perception following prolonged exposure to static face images reveal dynamic interactions in local cortical ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
104
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 28 publications
13
104
2
1
Order By: Relevance
“…Consistent with this perspective, recent behavioral (e.g. Teufel et al, 2009) and neural evidence (e.g. Coricelli and Nagel, 2009;Rice and Redcay, 2016) from adults suggests that on-going social interaction involves mental state inference-or mentalizingabout one's social partner.…”
Section: Introductionsupporting
confidence: 50%
“…Consistent with this perspective, recent behavioral (e.g. Teufel et al, 2009) and neural evidence (e.g. Coricelli and Nagel, 2009;Rice and Redcay, 2016) from adults suggests that on-going social interaction involves mental state inference-or mentalizingabout one's social partner.…”
Section: Introductionsupporting
confidence: 50%
“…Attention direction adaptation (Teufel et al, 2009) and automatic attention shifts by head orientation cues (Teufel et al, 2010a) has shown to be modulated depending on whether the participants were lead to believe that the other person was capable of seeing them or not via a video-link. Compatible with our previous propositions : Pönkänen et al, 2008, Teufel et al (2010b) proposed that mental-state attributions could modulate even the basic perceptual processing of social stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…As with Nuku and Bekkering's observations, this shows that gaze cueing can be modulated by the observers' beliefs about whether the agent can or cannot see. In a further study using mirrored goggles, Teufel et al (2009) employed a gaze perception aftereffect in which prolonged exposure to a face gazing in one direction altered subsequent perception of where the face was looking (Jenkins, Beaver, & Calder, 2006). Teufel et al (2009) reported that this effect was enhanced when the observer believed that the agent could see through the goggles.…”
mentioning
confidence: 99%
“…In a further study using mirrored goggles, Teufel et al (2009) employed a gaze perception aftereffect in which prolonged exposure to a face gazing in one direction altered subsequent perception of where the face was looking (Jenkins, Beaver, & Calder, 2006). Teufel et al (2009) reported that this effect was enhanced when the observer believed that the agent could see through the goggles. Langton (2009), however, has urged caution in concluding that mental state attribution modulates gaze effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation